Assessment of laundering practices of La Mesa Heights households based on environmentally sustainable laundering checklist with carbon fast-print equivalents - Dorado, Jose L.,III; Rayala, Maria Monica E. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
The general objective of the research was to analyze the sustainable laundering practices of households in La Mesa Heights based on the perspective of environmentally sustainable laundry practices. Specifically, the study aimed to: update the environmentally sustainable laundering practices checklist formulated by Baydo (2016), describe the laundering practices of households which launder clothes in-house, determine and estimate the carbon footprint of each household, determine if the laundering practices are sustainable based on the updated checklist, and identify other sustainable laundering techniques practiced by the households. Forty-seven (47) or 100% of the active households of La Mesa Heights participated in the study. The 47 households were characterized according to the type of machine used, the frequency of laundering, the load per washing cycle, the kind of detergent used, sorting practices, pre-treatment practices, drying practices, equipment used, water and energy consumption. The research determined that there are sustainable practices that the households perform, but then there are also some key sustainable practices that are not practiced like bulk laundry instead of small loads. The households are split with laundering in huge loads and small amounts, they mostly reuse the garments to the garment's maximum extent before washing. Majority of them sort their laundry but there is still a need to improve on the sorting with size and dirt to maximize efficiency. Some recycle the water that they use and all of the households utilize the sun's natural energy to dry selected garments.
Available to the general public.
Thesis (B.S. Clothing Technology)--University of the Philippines Diliman
Keywords: Laundry -- Research -- Philippines -- Quezon City; Laundry machinery -- Philippines -- Quezon City; Sustainable living -- Philippines -- Quezon City